Analysis of employee Motivation in Kantor Pelayaan Perbendaharaan Negara ( KPPN ) at Pontianak - B11106111, YULIS TIAWATI (Jurnal Manajemen Update, 2013)
This research entitles Influence Motivation Work in Kantor Pelayaan Perbendaharaan Negara ( KPPN ) at Pontianak. The problem in this research is how to motivate employee Kantor Pelayaan Perbendaharaan Negara ( KPPN ) at Pontianak, an how much relation employee motivation Kantor Pelayaan Perbendaharaan Negara ( KPPN ) at Pontianak, the purpose of is study was to find picture of employee motivatian Kantor Pelayaan Perbendaharaan Negara ( KPPN ) at Pontianak, and to know how much motivation relationship Kantor Pelayaan Perbendaharaan Negara ( KPPN ) at Pontianak. The research method used is survey research using questionnaires as data collection techniques. The population in this study were all employees and all employees kantor pelayanan perbendaharaan negara ( KPPN ) sample. Data were analyzed using statistic deskriptif analysis of the result of the questionnaire, answer and then processed, in presentation and presented in the form of tables. The result of this study concluded that employee motivation is in generally good category. Keywords : motivation work